Pengaruh Viral Markketing, Influencer, User Generated Content terhadap Purchase Intention Produk Skincare Skintific pada Media Sosial Tiktok di Mojokerto - Paramita, Fita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This study aims to analyze the effect of viral marketing, influencers, user generated content on the purchase intention of skintific skincare products on tiktok social media in Mojokerto. This study applies a non-probability sampling method with a purposive sampling approach. The research population consists of active TikTok users who know skincare skintific products and are at least 17 years old, with a total sample of 96 respondents obtained from an online questionnaire via Google Form. The collected data were analyzed using multiple linear regression with the support of SPSS 22 software. The results of this study indicate that viral marketing, influencers, and user generated content have a positive and significant influence on the purchase intention of skintific products in Mojokerto.